Kampanye Visual Makanan Khas Kota Palembang Berbahan Baku Ikan - Tegar Febriansyah; Mukhsin Patriansah; Aji Windu Viatra (Penerbit dan Percetakan, CV. Picmotiv, 2024)
Visual Campaign for Typical Palembang Food Made from Fish is the right step because the author wants to introduce and preserve Palembang's Typical Food Made from Fish to Generation Z. The main problem faced is that the existence of Palembang Typical Food is starting to be eroded by the influence of international foods such as western Korean food and dishes are starting to be forgotten by the younger generation, especially Generation Z. The main aim of this design is to introduce the heritage of Palembang City's Typical Food to Generation Z as part of Indonesia's cultural richness which needs to be preserved and created through motion. graphics as a problem solving step. The expected achievement and target of this design is that typical Palembang food made from fish is better known to generation Z and continues to exist amidst the development of various types of food products circulating in the current era of globalization.